2011
DOI: 10.1007/s00264-011-1392-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of low molecular weight heparin on the expression of osteogenic growth factors in human fracture healing

Abstract: Purpose Anticoagulant therapy with low molecular weight heparins (LMWH) and mechanical compression is considered the gold standard for the prevention of thrombosis. However, evidence exists that LMWHs impair bone metabolism. The aim of this study was therefore to analyse alterations in the expression of M-CSF, VEGF and TGF-ß1 after treatment with enoxaparin in patients with long bone fracture to investigate the effect of LMWH on human fracture healing. Methods A total of 81 patients with long bone fractures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous studies indicate a delay of callus remodelling due to thromboprophylaxis with UH and LMW heparin [ 9 , 17 ]. So far there is no study which investigated the effect of the new oral Factor Xa inhibitor rivaroxaban on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate a delay of callus remodelling due to thromboprophylaxis with UH and LMW heparin [ 9 , 17 ]. So far there is no study which investigated the effect of the new oral Factor Xa inhibitor rivaroxaban on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study of Sarahrudi et al was the first comparative systematic measurement of VEGF serum levels in patients receiving enoxaparin. In this study no significant difference of the VEGF expression was observed [ 57 ].…”
Section: Discussionmentioning
confidence: 84%
“…Finally, Sarahrudi et al [ 57 ] first analyzed the alterations in the expression of osteogenic growth factors in patients with long bone fracture treated with enoxaparin. They measured (M-CSF, VEGF and TGF- β1) after treatment with enoxaparin and they observed significant differences of the expression of growth factors without any influence on fracture healing process.…”
Section: Literature Reviewmentioning
confidence: 99%